Upaya Pemanfaatan Perpustakaan Sekolah Dalam Meningkatkan Minat Baca Siswa Di Sekolah Dasar Negeri 1 Pamengkang Kecamatan Mundu Kabupaten Cirebon - Ika Kartika; Ratna Purwati (Jurnal IAI Bunga Bangsa Cirebon, 2020)
The low interest in reading our society greatly affects the quality of the Indonesian nation, because with the low interest in reading it cannot know and follow the development of science and information in the world. With the library, it can give students an